2014
DOI: 10.1111/irel.12054
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Economic Risk and Occupational Choice

Abstract: This paper examines the effects of attitudes toward economic risk on occupational choice. Workers with a more favourable disposition toward economic risk have a higher probability of being employed in the more prestigious, high‐paying Professional and Administrative occupations. Potential biases associated with omitted genetic and family background factors are considered. The marked differential in attitudes toward economic risk between males and females, however, makes only a minor contribution to the conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…They showed that while risk averse men were more likely to choose paid employment than to be self-employed, there was no significant effect of risk preferences on women’s entrepreneurship decisions. Le et al (2014) showed that risk-seeking individuals in Australia had a higher probability of being employed in more prestigious, high paying professional and administrative occupations. One study looking at the relationship between risk preferences and occupational choice for the case of Ghana is the study by Falco (2014) .…”
Section: Introductionmentioning
confidence: 99%
“…They showed that while risk averse men were more likely to choose paid employment than to be self-employed, there was no significant effect of risk preferences on women’s entrepreneurship decisions. Le et al (2014) showed that risk-seeking individuals in Australia had a higher probability of being employed in more prestigious, high paying professional and administrative occupations. One study looking at the relationship between risk preferences and occupational choice for the case of Ghana is the study by Falco (2014) .…”
Section: Introductionmentioning
confidence: 99%